1990
DOI: 10.1177/002224379002700308
|View full text |Cite
|
Sign up to set email alerts
|

Ease of Message Processing as a Moderator of Repetition Effects in Advertising

Abstract: The study suggests that the effect of repeated advertising exposures on brand evaluations is moderated by the ease with which the advertising message is processed. Increasing exposures enhanced the effectiveness of a difficult appeal, increased then decreased the effectiveness of a moderately difficult appeal, and decreased then increased the effectiveness of an easy appeal. These outcomes support the premise that message effectiveness can be affected by the time available for message processing and the time r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(134 citation statements)
references
References 11 publications
2
123
0
1
Order By: Relevance
“…The brand name was constantly displayed on each scene. Repetition was varied, with the banner ads presented once for the no-repetition condition, three times for the low-repetition condition, and eight times for the highrepetition condition (Anand & Sternthal, 1990). Repetition was manipulated as a within-subject factor.…”
Section: Experiments Designmentioning
confidence: 99%
“…The brand name was constantly displayed on each scene. Repetition was varied, with the banner ads presented once for the no-repetition condition, three times for the low-repetition condition, and eight times for the highrepetition condition (Anand & Sternthal, 1990). Repetition was manipulated as a within-subject factor.…”
Section: Experiments Designmentioning
confidence: 99%
“…Therefore, online brand image was measured in this study by four online brand attitude items (bad-good, unpleasant-pleasant, unfavorable-favorable, dislike-like) adapted from the literature (e.g., Anand and Sternthal, 1990) and the online brand belief scale consisting of 15 items from Kwon and Lennon (2006) which address four dimensions (aesthetic appeal, navigation convenience, transaction convenience, and web site content) of perceived attributes of apparel specialty retailers' online stores. All online brand image items used 7-point scales with a higher score indicating a more positive image.…”
Section: Online Brand Imagementioning
confidence: 99%
“…The resource-matching hypothesis (RMH) states that when the resources allocated to processing an act of communication match those required for the task, the persuasive impact of a message is maximized (Anand & Sternthal, 1989). Other researchers have found evidence that the results of advertising exposure are greater if there is a ''match'' between the individual cognitive resources available (RA) and the cognitive resources required (RR) to process advertising messages (Anand & Sternthal, 1989;Breckler & Wiggins, 1991). Martin et al (2005) employed the complexity of advertising messages as an indicator of consumer perception and found that websites of medium complexity were evaluated more favorably than those of low or high complexity.…”
Section: Self-referencing and Verbal Complexitymentioning
confidence: 99%